HUBUNGAN RIWAYAT ANEMI PADA KEHAMILAN DENGAN KEJADIAN STUNTING PADA BALITA USIA 12-59 BULAN DI WILAYAH KERJA PUSKESMAS WONOASIH KOTA PROBOLINGGO - Rohkmah, Dwi Yani; Maria Veronika Widiatrilupi, Raden; Retnaningsih, Reny (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2024)
Stunting is a serious health problem in Indonesia, characterized by children's height being shorter than their age standard due to chronic malnutrition. Anemia in pregnant women, often caused by iron deficiency, is a major risk factor that can affect fetal growth and development. This study aims to examine the relationship between a history of anemia in pregnancy and the incidence of stunting in toddlers aged 12-59 months in the Wonoasih Community Health Center working area, Probolinggo City. This research used a cross-sectional study design involving 16 respondents selected by purposive sampling. Data analysis was carried out using the Chi Square Test to determine the relationship between variables. The results of the study showed that of the 16 respondents, 15 of them who had a history of anemia during pregnancy had toddlers with stunting. Meanwhile, only one respondent with a normal pregnancy had a toddler with normal nutritional status. The Chi Square Test results show a p-value of 0.000, which means the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. This shows that there is a significant relationship between a history of anemia in pregnant women and the incidence of stunting in toddlers. There is a significant relationship between a history of anemia in pregnant women and the incidence of stunting in toddlers aged 12-59 months in the Wonoasih Community Health Center working area.